2012
DOI: 10.1371/journal.pone.0032826
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Evolution of Mitochondrial but Not Nuclear Genomes of Hymenoptera: New Evidence from Crabronid Wasps

Abstract: Mitochondrial genes in animals are especially useful as molecular markers for the reconstruction of phylogenies among closely related taxa, due to the generally high substitution rates. Several insect orders, notably Hymenoptera and Phthiraptera, show exceptionally high rates of mitochondrial molecular evolution, which has been attributed to the parasitic lifestyle of current or ancestral members of these taxa. Parasitism has been hypothesized to entail frequent population bottlenecks that increase rates of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 90 publications
7
36
0
Order By: Relevance
“…We found that the mean d S of mt genes was about 7–9 times higher than that of nu genes. This magnitude is consistent with the well-established pattern of high d S in animal mt genes (Brown et al 1979; Johnson et al 2003; Caccone et al 2004; Lynch 2007; Kaltenpoth et al 2012). Although the products of nu OXHPOS genes are transported into mitochondria where they function, they are expected to show mean d S similar to the non-OXPHOS genes because the coding sequences reside in the nu genome.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that the mean d S of mt genes was about 7–9 times higher than that of nu genes. This magnitude is consistent with the well-established pattern of high d S in animal mt genes (Brown et al 1979; Johnson et al 2003; Caccone et al 2004; Lynch 2007; Kaltenpoth et al 2012). Although the products of nu OXHPOS genes are transported into mitochondria where they function, they are expected to show mean d S similar to the non-OXPHOS genes because the coding sequences reside in the nu genome.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the fundamental importance of OXPHOS to aerobic life, mt protein-coding genes are not highly conserved and evolve at rates that is 5–50 times that of typical nu genes in vertebrates (Lynch 2007). This increased rate has been observed in a range of animal species, including primates (Brown et al 1979), Galapagos tortoises (Caccone et al 2004), lice (Johnson et al 2003), Drosophila (Haag-Liautard et al 2008), wasps (Kaltenpoth et al 2012), and nematodes (Denver et al 2000). The rapid evolutionary rate of mt genomes may be due to their cell cycle-independent replication of mtDNA (Bogenhagen and Clayton 1977), increased exposure to mutagenic oxygen radical species (Beal 1996), lack of protective histones, and limited DNA repair capacity (Croteau and Bohr 1997).…”
Section: Introductionmentioning
confidence: 96%
“…Heraty et al., ; Sharkey et al., ; Klopfstein et al., ). The uncertainty near the base of the Vespina could also be explained by the comparatively long terminal branches (Figs and ), which may be indicative of elevated rates of molecular evolution within Apocrita, as has been demonstrated for mitochondrial sequences (Dowton and Austin, ; Castro et al., ; Kaltenpoth et al., ).…”
Section: Discussionmentioning
confidence: 82%
“…PCR products were purified by adding 4 lL of a 1 : 4 mixture of Exonuclease I (Fermentas) and Fast Alcaline Phosphatase (Fermentas) to each sample, heating them at 37°C for 30 min, and then at 80°C for 15 min. Cleaned PCR products were sequenced in both directions with the original PCR primers and/or internal sequencing primers (Table 1), using the BigDye Ter- Table 1 Primers used for PCR and sequencing, with information provided on respective gene fragment, primer name, direction (forward, F or reverse, R) and location (internal, i or external, o) (Katoh et al, 2005) and/or by eye for determining exon and intron regions. Introns were identified in all nuclear genes, based on the presence of GT-AG splicing sites, and then deleted from the final alignments.…”
Section: Dna Extraction Pcr and Sequencingmentioning
confidence: 99%
“…The long branch leading to the Tantulocarida could be explained by a accelerated evolutionary tempo that might be typical for parasitic taxa (Dowton and Austin 1995;Page et al 1998). Although recent investigations show that this statement may be far from always true (Gilman et al 2012;Kaltenpoth et al 2012).…”
Section: Resultsmentioning
confidence: 99%